Ética y Política - Gonzales Casas, Miguel Angel (2021)
When we talk about human beings, it is impossible to ignore the links they have with their peers and with society itself. That is to say, the human being since his appearance in this world is a social being, which makes living in this world pleasant and fruitful, because in some way we share, we can learn from each other, as well as share experiences, emotions, knowledge, etc. However, relating with others has not always been easy, since the individual has as we know their own interests, different ways of seeing reality, different temperaments and different moral principles; with which the individual to live in society can often be a chaos. In this sense, the study of ethics is important, since in general terms it is the study or reflection on morality, on human conduct, on what is good or bad. That is to say, ethics as a philosophical discipline seeks to help human beings to live harmoniously with others. We mentioned that coexistence in society often does not result in a peaceful way, not all people stop to reflect on moral issues; that is why it is essential that there is a relationship between ethics and politics, since in essence both seek the same goal, the good. Politics at this point plays a very important role because, through the functions of power, certain norms and laws are established that can guarantee life in a just, peaceful and organized society. In this way, it is important to develop the session entitled "Ethics and Politics" which is aimed at students in 5th year of secondary education, in the area of Personal Development, Citizenship and Civics, it seeks that students recognize, analyze, reflect and deepen their knowledge on the subject.